FORMULASI DAN EVALUASI SEDIAAN TABLET ASAM MEFENAMAT MENGGUNAKAN EKSIPIEN CROSCARMELLOSE SODIUM SEBAGAI DISINTEGRAN DENGAN METODE GRANULASI BASAH - Garnadi, Jafar (P3M STIKes Bakti Tunas Husada, 2019)
Mefenamic acid is a class of NSAIDs (Non-Steroid Antiinflammatory) which belongs to BCS group (Biopharmaceutical Classification System) class II that is low solubility with high penetration membrane. So it is necessary to increase the solubility to get absorption that can penetrate the maximum therapeutic zone of reagent. This study aims to determine the effect of the concentration of disintegran Croscarmellose sodium with a concentration of 1% - 5% on the physical quality and dissolution rate because it has a working mechanism of water absorption (water wicking) and swelling rapidly. Raw material collection, manufacture of mefenamic acid tablets (the wet granulation method is used because it can improve the flow rate and the compressibility of the mefenamic acid), evaluation of mefenamic acid granules, evaluation of mefenamic acid tablets, data analysis using one way ANOVA. Characterization of physical quality of granules moisture content, flow rate, fixed angle according to requirements. Characterization of quality tablet hardness, friability, frixibility, weight, uniformity size, disintegration time, and dissolution according to requirements.. Statistical analysis, indicating that there are significant differences in hardness, weight, uniformity of size, crushed time, rate and dissolution. From the results of this study can be concluded that the formula with a concentration of Croscarmellose Sodium 5% gives the best results. Keywords: Mefenamic acid, Croscarmellose sodium, Wet granulation, Physical quality, Dissolution rate..